CAUSAL DE TERMINACIÓN DE CONTRATO A TRAVÉS DEL VISTO BUENO POR PARTE DEL TRABAJADOR - Chamba Auquilla, Angie Paulina (2019)
The research topic is "The cause of approval proposed by the worker to the employer", within the work code, which is thoroughly analyzed the Approval, concept, history, complete procedure to apply to the Labor Inspector and incidence in the work judgment; the grounds for terminating the Work Contract, according to articles 169, 172 and 173 of the Labor Code, the advantages and disadvantages for the employer and worker. In addition, in Ecuador there is a legal vacuum in terms of the legal regulation of employer default, which has led to a large number of cases are in hiding, not being reported by the victims, mainly because there is no specific legal basis in which they can protect themselves; within the company there may exist, as in fact there are, workers who bear unfair treatment against their well-being, health, opportunities and other fundamental rights, which are inherent in them because they are protected by the Constitution of the Republic, so that with the present work it is intended to make known what are the best mechanisms to enforce the rights of the worker regarding the timely deposit of the employer's contribution to the IESS. Therefore, it is necessary that the State, by rule, regulate these issues in order to avoid excesses on the part of certain employers, therefore the corresponding Bill of Amendment to the Labor Code is presented.